2007
DOI: 10.1128/iai.00397-07
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Farnesol Interferes with the Normal Progression of Cytokine Expression during Candidiasis in a Mouse Model

Abstract: Candida albicans, a dimorphic fungus composed of yeast and mycelial forms, is the most common human fungal pathogen. Th1 cytokines such as interleukin-2 (IL-2), gamma interferon (IFN-␥), and tumor necrosis factor alpha (TNF-␣), which are induced by macrophage IL-12, are critical to resistance against systemic candidiasis, while Th2 cytokines such as IL-4 and IL-5 are less critical. Farnesol is a quorum-sensing molecule produced by C. albicans that controls the formation of mycelia but is also a virulence facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
71
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(73 citation statements)
references
References 57 publications
2
71
0
Order By: Relevance
“…Our data strengthened previous observations about an important role of isoprenoids in inflammation (8,(21)(22)(23)(24)(25), even if they do not explain how isoprenoids mediate this event. These compounds play an important role in different biological function, including protein prenylation and production of steroid hormones and biologically active terpenes.…”
Section: Discussionsupporting
confidence: 76%
“…Our data strengthened previous observations about an important role of isoprenoids in inflammation (8,(21)(22)(23)(24)(25), even if they do not explain how isoprenoids mediate this event. These compounds play an important role in different biological function, including protein prenylation and production of steroid hormones and biologically active terpenes.…”
Section: Discussionsupporting
confidence: 76%
“…We have shown that it blocks the yeast to mycelium transition in C. albicans, 3 acts as a virulence factor in a mouse model of systemic candidiasis, [10] and [11] probably by interfering with the normal progression of cytokine expression in their immune response, 12 and triggers apoptosis in the fungus Aspergillus nidulans. 22 Others have shown that farnesol alters circadian rhythms in Neurospora crassa and targets HMG CoA reductase for proteolysis in both Saccharomyces cerevisiae and Chinese hamster ovary cells.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the availability of molecules such as tetrazole 5 (a potent quorum-sensing molecule which enhances pathogenicity) and 10 (a potent quorum-sensing molecule which does not enhance pathogenicity) may provide a potent tool in understanding how farnesol functions as a virulence factor in interactions with cellular macrophages and CD4 T cells to alter adaptive immunity. 12 The analogs also provide a means of establishing differences and similarities between farnesol's effect on virulence and its ability to block both hyphal development and biofilm formation. [3] and [29] Along these lines, it is interesting to note that an analog of triazole 10 bearing five additional carbons has been reported to be a potent activator of protein kinase C. 20 Of course, the differences in the pathogenicity of C. albicans observed in the presence of farnesol, 5, and 10 could also be due to differing pharmacokinetics or their differing influence on mouse cytokine production.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations